1974
DOI: 10.1021/i160051a002
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Kinetic Studies of Solvent and Substituent Effects on Diels-Alder Reactions

Abstract: The radiofrequency (1-20 MHz) ozonizer discharge or "chemical corona" has been compared in its operation in oxygen to the same device operated at 60 Hz. Comparable chemical, energetic, and electrical data were taken. In the high-frequency regime where the behavior of the discharge is dominated by a steady-state accumulation of excess positive ions in the gap, the best energy efficiency is several orders of magnitude worse than at low frequencies. A simple model, assuming minimization of the rate of production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1974
1974
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…This result is similar to those of high-pressure kinetic studies in the liquid state in that a change in pressure of many hundreds of bars is required to achieve a significant change in the rate constant. For example, the rate constant for the DielsAlder reaction of chloroprene and maleic anhydride changes only by a factor of 5.8 in acetone at 65OC for a change in pressure of 1,400 bar (McCabe and Eckert, 1974).…”
Section: Solvent Effect On Rate Constants At Supercritical Fluid Condmentioning
confidence: 99%
“…This result is similar to those of high-pressure kinetic studies in the liquid state in that a change in pressure of many hundreds of bars is required to achieve a significant change in the rate constant. For example, the rate constant for the DielsAlder reaction of chloroprene and maleic anhydride changes only by a factor of 5.8 in acetone at 65OC for a change in pressure of 1,400 bar (McCabe and Eckert, 1974).…”
Section: Solvent Effect On Rate Constants At Supercritical Fluid Condmentioning
confidence: 99%
“…Considering DARs as an isopolar process 1,2,9, it is difficult to explain why the transition state with a partial CC bonding should be more compact than that of the cycloadduct 10–16.…”
Section: Introductionmentioning
confidence: 99%
“…For this reaction in other solvents it was found that V = retro < 0 and V = forw / V r-n > 1 [11,31]. In the DAR with maleic anhydride, the "normal" relationship V = retro > 0 and V = forw / V r-n < 1 in acetonitrile and ethyl acetate, and the "abnormal" relationship in other solvents V = retro < 0 and V = forw / V r-n > 1, were obtained [18][19][20]. Different solvent accessibility is the reason for the large differences in the values of PMV of branched structures of adamantane (136.9 and 142.7) and congressane (160.2 and 177.4 cm 3 ·mol −1 ) in n-hexane and benzene [32].…”
Section: Resultsmentioning
confidence: 96%
“…There are only a few direct measurements of the pressure influence on the rate of adduct decomposition [8,[15][16][17]. Why the AC in isopolar DAR should be more compact than the cycloadduct is not yet understood [15][16][17][18][19][20].…”
mentioning
confidence: 99%